Readability Assessment of Reading Texts in Pathway to English for SMA/MA Grade X - Lumepa, Rara Anggreiny; Tuna, Jim Ronny; Andries, Fivy A (KOMPETENSI, 2022)
The purpose of the study is to describe readability of reading texts in textbook, ‘Pathway to English’ for SMA/MA Grade X’ published by Erlangga. The study is a quantitative content analysis. The source of the data was the textbook, and only reading texts with minimally 150 words in length were taken as the sample. 22 reading texts that matched the criteria were analyzed quantitatively in percentage form. Result of the data analysis shows that reveals that 9 (or 41%) reading texts match tenth grade level, but the rest, 4 (or 18%) reading texts are to easy, at 7th-8th grade level. and 9 (or 41%) reading texts are are fairly difficult to difficult, at 11th-16th grade level. Put it another way, 59% reading texts with minimally 150 words in length selected for use in EFL textbook ‘Pathway to English’ published by Penerbit Erlangga in 2016 were not in accordance with tenth grade SMA students’ readability level. In addition, It was also found that the data show that readability level of a text do not depend on text length.